Efektifitas Penyelesaian Sengketa Konsumen Melalui Proses di Luar Pengadilan (Melalui Jalur Mediasi) - Apriliani Kusnadi; Devi Siti Hamzah Marpaung (Universitas Batanghari Jambi, 2022)
A civil dispute in an agreement is a case that arises from an agreement that has been previously agreed upon by the parties. An agreement that starts from negotiation to produce an agreement that is written on a trading contract. The current condition shows that dispute resolution in court is no longer the main choice because it is considered not effective and efficient enough. The choice of dispute resolution through an arbitration institution is considered to provide its own advantages over going through a national court. And the neglect of consumer rights can invite losses that lead to consumer disputes. So the purpose of this main discussion is how the process of resolving consumer disputes based on UUPK and the process of resolving disputes through mediation channels. The research method is normative law, and obtains data by using secondary data based on legal provisions and periodic legal developments. The choice of dispute resolution through the UUPK can be resolved through court (litigation) and out-of-court (non-litigation) channels. And it has been explained in Article 48 of the UUPK that